Comparative Evaluation of the Antiglycation and Anti-α-Glucosidase Activities of Baicalein, Baicalin (Baicalein 7-O-Glucuronide) and the Antidiabetic Drug Metformin - Guglielmina Froldi; Francine Medjiofack Djeujo; Nadia Bulf; Emma Caparelli; Eugenio Ragazzi (MDPI AG, 2022)
The discovery of new oral antidiabetic drugs remains a priority in medicine. This research aimed to evaluate the activity of the flavonoid baicalein and its natural glucuronide baicalin, compared to the antidiabetic drug metformin, as potential antiglycation, anti-radical, and anti-α-glucosidase agents, in order to assess their potential role in counteracting hyperglycemia-induced tissue damage. The study considered: (i) the BSA assay, to detect the formation of advanced glycation end products (AGEs), (ii) the GK peptide-ribose assay, which evaluates the cross-linking between the peptide and ribose, and (iii) the carbonyl content assay to detect the total carbonyl content, as a biomarker of tissue damage. In addition, to obtain a reliable picture of the antiglycation capacity of the investigated compounds, DPPH scavenging and oxygen radical absorbance capacity (ORAC) assays were performed. Furthermore, the anti-α-glucosidase activity of baicalein and baicalin was detected. Furthermore, to estimate cell permeability, preliminarily, the cytotoxicity of baicalein and baicalin was evaluated in HT-29 human colon adenocarcinoma cells using the MTT assay. Successively, the ability of the compounds to pass through the cytoplasmic membranes of HT-29 cells was detected as a permeability screen to predict in vivo absorption, showing that baicalein passes into cells even if it is quickly modified in various metabolites, being its main derivative baicalin. Otherwise, baicalin per se did not pass through cell membranes. Data show that baicalein is the most active compound in reducing glycation, α-glucosidase activity, and free radicals, while baicalin exhibited similar activities, but did not inhibit the enzyme α-glucosidase.